Significance of PD1 Alternative Splicing in Celiac Disease as a Novel Source for Diagnostic and Therapeutic Target - Ponce de León, Candelaria; Lorite, Pedro; López-Casado, Miguel Ángel; Barro, Francisco; Palomeque, Teresa; Torres, María Isabel (Frontiers in Immunology, 2021)
Background: We have focused the alteration of PD-1/PD-L1 pathway in celiac disease and discuss the roles of the PD1 pathway in regulating the immune response. We have explored the idea that the altered process of mRNA splicing in key regulatory proteins could represent a novel source for the identification of diagnostic, prognostic and therapeutic targets in celiac disease. Methods: We have characterized PD1 mRNA variants profile in CD patients and in response to gluten peptides incubation on in vitro experiments. Total RNA from whole blood was isolated and the amplification of the coding region of the human PD-1 mRNA was performed by cDNA PCR. Results: PCR amplification of the human PD-1 coding sequence revealed a correlation between the over-expression of the sPD-1 protein and the PD-1Δex3 transcript in celiac disease. Thus, we have found three novel isoforms of alternative spliced, two of them result in a truncated protein and other isoform with loss of 14 aa of exon 2 and complete exon 3 (Δ3) could encodes a new soluble form of PD1 (sPD-1). Conclusions: Our study provides evidences that dietary gluten can modulate processes required for cell homeostasis through the splicing of pre-mRNAs encoding key regulatory proteins, representing an adaptive mechanism in response to different nutritional conditions.